Breaking up with Brueghel. - Brownell, Mia (2011)
A sabbatical project, "Breaking up with Brueghel," led to creation of an extensive number of paintings. Their common theme was the correlation between structures of life as depicted in molecular imaging and the structures of art in still life painting. The tradition of food as a subject of still life paintings was re-examined through the genetics of food. The paintings were exhibited in a number of venues, including several abroad, and purchased by donors for various musea and galleries. The accompanying leaflet presents one of the paintings.
Keywords: dept.art; faculty_collection; sabbatical_report

Landscapes of Order, Landscapes of Memory: Italian-American Residential Landscapes of New York Metropolitian Region - Inguanti, Joseph J. (Italian Folk: Vernacular Culture in Italian-American Lives, 2011)
Keywords: Folklore; Italian Americans; Italian Americans; Social life and customs; dept.art; faculty_collection

Frans Hals and the Vernacular - Levine, David A. (The Transformation of Vernacular Expression in Early Modern Arts, 2011)
"Frans Hals and the Vernacular" published on 01 Jan 2012 by Brill.
Keywords: dept.art